MENGENAL PEMIKIRAN YVES CONGAR: Sebuah Refleksi Ekumenis dalam Konteks Gereja Kristen Jawa - Yudo Aster Daniel (Marturia, 2021)
AbstractTheology is a fact of life in which it must respond to the times, and therefore always needs reflection and renewal. One of them is to build relations between the Catholic and Christian churches in the ecumenical movement. One of the Catholic figures, as well as an early pioneer of the ecumenical movement, was Yves Congar. Even because of the movement, Congar had received ecclesiastical tactics from the Vatican Rome. The ecclesiological view that underlies the Congar ecumenical movement focuses on the divine and human dimensions of the church, which over time has an impact on the tension between the two. For Congar the core of ecclesiology is Ecclesia de Trinitate, Ecclesia ex Hominibus, and Ecclesia in Christo. Congar's theological view has similarities with the teachings in Pokok-pokok Ajaran Gereja Kristen Jawa (PPA GKJ). Recognizing Congar's ecumenical thoughts and reflecting on the context of the GKJ will enrich insight into the ecumenical movement in Indonesia. Abstrak Teologi adalah kenyataan hidup di mana ia mesti menyikapi perkembangan zaman, dan karena itu selalu membutuhkan refleksi dan pembaruan. Salah satunya adalah dengan membangun relasi antara gereja Katolik dan Kristen dalam gerakan ekumenisme. Salah satu tokoh Katolik, sekaligus perintis awal dari gerakan ekumenis, adalah Yves Congar. Bahkan karena gerakan itu, Congar pernah mendapat siasat gerejawi dari Vatikan Roma. Pandangan eklesiologi yang mendasari gerakan ekumenis Congar berfokus pada dimensi ilahi dan insani dalam gereja, di mana seiring perkembangan zaman berdampak pada ketegangan antara keduanya. Bagi Congar inti dari eklesiologis adalah Ecclesia de Trinitate, Ecclesia ex Hominibus, dan Ecclesia in Christo. Pandangan teologis Congar ini memiliki kemiripan dengan ajaran dalam Pokok-pokok Ajaran Gereja Kristen Jawa (PPA GKJ). Mengenali pemikiran ekumenis Congar dan merefleksikan dalam konteks GKJ akan memperkaya wawasan mengenai gerakan ekumenisme di Indonesia.